A mechanistic study of electrode materials for rechargeable batteries beyond lithium ions by in situ transmission electron microscopy. Issue 5 (1st April 2021) - Yousaf, Muhammad; Naseer, Ufra; Li, Yiju; Ali, Zeeshan; Mahmood, Nasir; Wang, Lei; Gao, Peng; Guo, Shaojun
Abstract : This article summarizes the real-time information on electrodes, electrolytes and their interfaces of various rechargeable battery systems including heavier alkali ion, lithium-sulfur, alkali-metal oxygen and all-solid-state batteries made by in situ transmission electron microscopy. Abstract : Understanding the fundamental mechanisms of advanced electrode materials at the atomic scale during the electrochemical process is necessary to develop high-performance rechargeable batteries. The complex electrochemical reactions involved in a running battery, which cause intensive structural and morphological changes in electrode materials, have been explored to a certain extent by the use of real-time characterization techniques. In situ transmission electron microscopy (TEM) is one of the most noteworthy diagnostic techniques to understand and monitor dynamic electrochemical processes because of its atomic-scale resolution and real-time monitoring, which can provide information about chemical and physical characteristics. In this review, the current progress in the development of electrode materials using in situ TEM for rechargeable batteries beyond the lithium ion is summarized. First, the various battery designs used for in situ TEM and their challenges are elaborated. Afterward, we systematically summarize the basic science and fundamental reactions including phase transformation and electrode/electrolyte interfaces in electrode materials for heavier alkali ion (sodium, potassium calcium and magnesium) batteries (H-AIBs). Particularly, the real-time insights into three types of electrochemical mechanisms: intercalation, alloying, and conversion reactions are elaborated. Moreover, in situ electrode chemistry in lithium sulfur (Li–S) batteries, alkali-metal oxygen batteries (AOBs) including lithium, sodium and potassium oxygen batteries, and all-solid-state batteries (ASSBs) is also discussed. Finally, we provide a summary and future perspective of in situ TEM in rechargeable batteries along with the most feasible electrode design.